Lateral Limit of Superior Sagittal Sinus in Respect to External Part of Sagittal Suture - Nepal, Pankaj Raj; Magar, Birat Thapa (Eastern Green Neurosurgery, 2020)
Background: Sagittal suture has been used as an external landmark of superior sagittal sinus since the very beginning of neurosurgery. However, most of the time the sinus is not exactly under the suture line, rather, it has some displacement to one side. So, to analyze the variation of the lateral limit of superior sagittal sinus from the external part of sagittal sinus this study was performed.Materials and methods: Consecutive cases of MRI brain with contrast done in B&C Medical College Teaching Hospital was collected over 3 months, Age, gender, right, and left lateral limits of the superior sagittal sinus from the sagittal suture at its mid-point was collected in preformed proforma. Mean and standard deviation was calculated for the continuous variables, ANOVA was done to evaluate the association of gender with the lateral limits of sinus and Pearson correlation was done to see the relation of age with the lateral limits of the sinus. All the analysis was done using IBM SPSS 20.Results: There were a total of 40 patients enrolled in the study. The mean age was 39.8 years with male (75%) predominance. The lateral right limit of the superior sagittal sinus was up to 23mm and in the left up to 17.1mm from the outer limit of the sagittal suture. There was no significant association of gender with both the right and left limits of the superior sagittal sinus. Similarly, there was no significant correlation of age with the lateral limit of the superior sagittal sinus.Conclusion: The mean existence of superior sagittal sinus is 9.57mm in the right to 5.78mm in the left side from the outer limit of the sagittal suture. However, in extreme stances it's lateral limits can extend up to 17mm in left to 23mm in the right from the outer limit of the sagittal suture.